Arthroscopic Management of an Extremely Rare Wrist Fracture-Dislocation Pattern - Corella, Fernando; Ocampos, Montserrat; Collado, Carlos; Laredo, Rafael (Journal of Wrist Surgery, 2024)
Axial dislocation involves the displacement of carpal bones along the longitudinal axis of the wrist joint. There are three major groups: (1) axial ulnar, (2) axial radial, and (3) combined. On the other hand, radiocarpal dislocation entails disruption of the articulation between the radius and carpal bones. There are two groups: (group 1) it is either a pure radiocarpal dislocation or a minor avulsion of the radial styloid and (group 2) a fracture-dislocations characterized by a significant radial styloid fragment.The patient, a 66-year-old female involved in a car accident, underwent imaging studies and arthroscopic exploration, revealing a transcapitate perihamate translunate fracture-dislocation, associated with a radiocarpal dislocation type 1. Arthroscopic treatment was performed through common dorsal radiocarpal and midcarpal portals, along with the volar radial portal. Anatomical reduction of the joints and fractures was achieved under arthroscopic control, along with suturing of the volar radiocarpal ligaments.The simultaneous occurrence of axial dislocation and radiocarpal dislocation, as observed in our case, is exceedingly rare and lacks comprehensive documentation in the existing literature. Furthermore, the specific type of axial dislocation (transcapitate perihamate translunate) has not been previously reported.Various treatment approaches, including closed reduction, open reduction, and external fixation, have been described for these types of complex pathologies, but few reports describe their arthroscopy management.This case report describes a rare occurrence of axial ulnar dislocation associated with radiocarpal dislocation of the wrist, which is exceptionally uncommon and not reported previously in the literature. This arthroscopic approach yielded excellent results, avoiding the need for multiple open approaches to address several fractures and ligament injuries.
Keywords: axial dislocation; radiocarpal dislocation; wrist arthroscopy.